β-Naphtoflavone and Ethanol Induce Cytochrome P450 and Protect towards MPP+ Toxicity in Human Neuroblastoma SH-SY5Y Cells - Fernandez-Abascal, Jesus; Ripullone, Mariantonia; Valeri, Aurora; Leone, Cosima; Valoti, Massimo (International journal of molecular sciences, 2018)
Cytochrome P450 (CYP) isozymes vary their expression depending on the brain area, the cell type, and the presence of drugs. Some isoforms are involved in detoxification and/or toxic activation of xenobiotics in central nervous system. However, their role in brain metabolism and neurodegeneration is still a subject of debate. We have studied the inducibility of CYP isozymes in human neuroblastoma SH-SY5Y cells, treated with β-naphtoflavone (β-NF) or ethanol (EtOH) as inducers, by qRT-PCR, Western blot (WB), and metabolic activity assays. Immunohistochemistry was used to localize the isoforms in mitochondria and/or endoplasmic reticulum (ER). Tetrazolium (MTT) assay was performed to study the role of CYPs during methylphenyl pyridine (MPP+) exposure. EtOH increased mRNA and protein levels of CYP2D6 by 73% and 60% respectively. Both β-NF and EtOH increased CYP2E1 mRNA (4- and 1.4-fold, respectively) and protein levels (64% both). The 7-ethoxycoumarin O-deethylation and dextromethorphan O-demethylation was greater in treatment samples than in controls. Furthermore, both treatments increased by 22% and 18%, respectively, the cell viability in MPP+-treated cells. Finally, CYP2D6 localized at mitochondria and ER. These data indicate that CYP is inducible in SH-SY5Y cells and underline this in vitro system for studying the role of CYPs in neurodegeneration.